Sanctuary in the Midst of Crisis? A Look into Shariah Indices using Multivariate GARCH DCC - Syed Aun Raza Rizvi; Shaista Arshad (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2013)
Islamic Finance has evolved over the past few decades, and stands at over a trilliondollars today. At the foundations of Islamic finance lay the concept of risk sharing, and the purest forms of it in the modern day finance is equity investments. The evidence of Islamic investors pursing equity investments in reality is thin. Multitude of reasons are attributed to this low participation, mainly revolving around lack of empirical proof of Islamic investments being a reliable and steady return alternative. This study is an attempt to study the volatilities and correlations with the conventional global equity indices utilizing Multivariate GARCH Dynamic Conditional Correlations (MGARCH DCC) method. The findings provide an interesting angleto our study, where there is a significant downwards trend in the correlations during the crisis era. This provides substance to the argument that Islamic investors would experience lesser downside in economic crisis. This study further dwells into the linkage of Islamic indices with global financial indices to study if financial sector exclusion from Islamic indices benefits theinvestors. The findings are positive, with lower correlations and that to reducing in the recent global crisis. Islamic finances core philosophy is equity based investments and this study is a humble attempt to empirically substantiate its benefits.